The effects of speed endurance training vs. aerobic high-intensity intervals on endurance performance in elite Danish orienteers - Rokkedal-Lausch, T.; Lassen, T.; Larsen, R. G.; Madsen, K.; Franch, J. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: It is well-known that a short-term period of high intensity training (HIT) is effective in improving endurance performance in trained athletes(Laursen & Jenkins 2002). However, only few studies have been performed in highly trained endurance athletes and therefore the knowledge about the effects of different types of HIT in elite athletes is sparse(Kilen et al., 2014; Denadai et al., 2006). The purpose of the present study was to evaluate five weeks of speed endurance running (SET, n=8) or aerobic high-intensity running (AHI, n=5) in elite orienteers. Methods: Performance measures included a short intermittent (4000m) and a field running endurance performance test (8000m), VO2max and running economy (RE). Further, blood samples pre and post was evaluated for markers of muscle damage and overreaching (LDH, CK, myoglobin, cortisol) and session rating of perceived exertion (session-RPE) was collected after every HIT session. Thirteen elite orienteers (7 female, 6 male), with mean VO2max of 61.9 ± 3.3 ml O2/min/kg and RE of 195 ± 3.2 ml O2/min/km performed either SET or AHI two to three times weekly for five weeks combined with regular aerobic low-intensity training. In both groups overall running distance was reduced by 20% compared to the four weeks prior to intervention. SET consisted of 4-12x30- sec. at 90-100% of maximal running distance during a 30-second sprint with 3 minutes of active recovery. AHI consisted of 4-8x4min intervals at an average of 90% of maximal heart rate with 2 minutes of active recovery. Results: We found no significant differences in relative changes between groups in running performance, VO2max and running economy. Short intermittent endurance performance was maintained whereas long endurance performance showed a tendency towards being impaired in both groups. When combining the groups there was a significant improvement in running economy performance (P < 0.05). VO2max was reduced in both SET and AHI (P < 0.05) whereas maximal lactate accumulation (Lamax) increased (P < 0.05). Session-RPE was significantly higher in AHI than in SET (P < 0.05) while no changes were observed in markers of muscle damage and overreaching. Conclusion: In conclusion, five weeks of SET or AHI, impaired long field running performance and VO2max while short intermittent running performance was maintained and RE improved.